Knowledge of the properties of the Qur’anic verses: Its inception, stages of development, and controls - Sior, Ali (Jordan Journal of Islamic Studies, 2023)
This study tackles the issue of the effect of reading the Qur’an on bringing benefits and advancing disadvantages, such as the effect of reading some verses regarding the detection, nullification, and payment of magic. Including those related to bringing a livelihood and its capacity. Including what is related to the enemy’s response and defeat. Including those related to returning the absentee and achieving his security. Including what is related to the preservation of the house and the goods ... and other types that have been mentioned a lot, which are related to the matters of the apparent, the inner, the lower, and the afterlife, and the research is subject to the legal rooting for him and a statement of his legitimacy evidence from the book and the Sunnah, and then he mentioned the conditions and controls that he should adhere to Desiring to deal with the Qur’anic verses in order to achieve its demands by bringing or pushing, and the research concluded a set of results from it, proving the properties of the Qur’an by bringing benefits and pushing the harms of the Holy Quran and the Sunnah of the Prophet Including the validity of the expansion by choosing verses for the purpose of bringing benefits and paying harm to them. And that it is not required with reading the Qur’anic verses to achieve this characteristic except for reading it, because the characteristic of the Qur’an is not something else outside the verse of the Qur’an. And that this science, i.e. the science of the properties of the Qur’an, is one of the sciences that should be taken care of because it has effects that benefit the Muslim in particular, and because it contains proof of a form of the miracle of the Noble Qur’an and thank Allah the god of everything.